Malay translation, validation and . reliability of hypersensitivity to sound (giif) questionnaire: a preliminary study - Ihsan, Nurakmal Zarith Badrul (Universiti Sains Malaysia, 2016)
Prevalence of hyperacusis, especially in Malaysia population has not been widely searched. A questionnaire name Gerauschuberempfindlickeits (GUF) questionnaire was developed to identify the levels of subjective distress related to hyperacusis. The aim of this study is to translate and validate a Malay version of Hypersensitivity to Sound (GUF). This is important to be used in Malaysian population, where majority of the people speaks in the Malay language. Thirty respondents were involved. They were selected randomly among students and staffs of Health Campus, USM. Forward and backward translation were completed on the questionnaire, as well as content validity and reliability analysis. Total agreement for forward and backward translation are 85% respectively. Content validity revealed few item scored <3.5 and suitable amendment had been done to improve the questionnaire. Face validity revealed majority of participants agreed that language used is appropriate, questionnaire is easy to understand and vocabulary used is suitable among Malay-language users. The total Cronbach’s alpha (a) value obtained upon calculation was 0.899, which is closely similar to previous findings in other languages; German a - 0.89 (Nelting et.al, 2002), Spanish a = 0.90 (Herraiz C. et. al., 2006) and English a = 0.889 (Adhiyah S., 2014). The alpha a values for each domains are cognitive reactions to hyperacusis (KRH) a = 0.889, somatic behaviour (ASV) a = 0.776 and emotional reaction (ERG) a = 0.899. The overall a value of Malay version of GUF questionnaire is reliable and considered good. However, the questionnaire needed to be tested on hyperacusis patients to further validate it. In conclusion, the findings in this preliminary study of Malay version of Hypersensitivity to Sound (GUF) questionnaire can be used to further validate the questionnaire among hyperacusis patients Malaysian population who understand Malay language.